Eating Disorders and Intrasexual Competition: Testing an Evolutionary Hypothesis among Young Women - Abed, Riadh (The Scientific World Journal, 2012)
The sexual competition hypothesis (SCH) contends that intense female intrasexual competition (ISC) is the ultimate cause of eating disorders. The SCH explains the phenomenon of the pursuit of thinness as an adaptation to ISC in the modern environment. It argues that eating disorders are pathological phenomena that arise from the mismatch between the modern environment and the inherited female adaptations for ISC. The present study has two aims. The first is to examine the relationship between disordered eating behavior (DEB) and ISC in a sample of female undergraduates. The second is to establish whether there is any relationship between disordered eating behavior and life history (LH) strategy. Participants completed a battery of questionnaires examining eating-related attitudes and behaviors, ISC, and LH strategy. A group of 206 female undergraduates were recruited. A structural equation model was constructed to analyze the data. ISC for mates was significantly associated with DEB, as predicted by the SCH. DEB was found to be predicted by fast LH strategy, which was only partially mediated by the SCH. The results of this study are supportive of the SCH and justify research on a clinical sample.